Math, asked by imsadiafatima11, 1 year ago

the solution of px+qy=p-q and qx-py=p+q is

Answers

Answered by raghuvanshiji
2

Answer:

tep-by-step explanation:

Given:

Px+Qy=P-Q......(1)

Qx-Py=P+Q......(2)

Now multiplying equation (1) with P and equation (2) with Q we get

Px+Qy=P-Q×P

Qx-Py=P+Q×Q

=P×Px+PQy=P×P-QP.....(3)

Q×Qx-PQy=P×Q+Q×Q....(4)

Now by adding equation (3) and (4) we get

(Psquare+Qsquare )x=Psquare+Qsquare

Implies x= Psquare+Qsquare /Psquar+Qsquare

Which implies x=1

Consider PX+Qy=P-Q

=P(1)+Q(y)=P-Q

=P+Qy=P-Q

=Qy=P-Q-P

=y=-Q/Q

=y=-1

Therefore the value of x=1 and y=-1

Similar questions